(untitled) (GYMNASIUM, 2009)
This paper aims to highlight the requirements of the code’s score FI.G. samples "beam" and a number of specific directions in this device leading to a new approach to the selection process to increase capacity performance gymnasts. Sample beam is the most demanding test of female gymnastics Allround Speed Skating. The result obtained from this device influence determining the final outcome in the contest or AA Team.